POLA DISTRIBUSI TUMBUHAN PAKU (Pteridophyta) DI KAWASAN HUTAN KEMASYARAKATAN DUSUN PEMOTOH DESA AIK BERIK KECAMATAN BATUKLIANG UTARA KABUPATEN LOMBOK TENGAH NTB - Asri, Indra Himayatul; Fajri, Nurul (Cocos Bio, 2022)
The purpose of this study was to determine the Distribution Pattern of Nail Plants (Pteridophyta) in the Community Forest Area of Pemotoh Hamlet, Aik Berik Village, North Batukliang District, Central Lombok Regency, NTB. This type of research is a quantitative descriptive study. The data collection instrument regarding the types of ferns in this study used an observation sheet or observation sheet. The observation sheet in the form of a table is used as a place to record the results of observations to determine the number of types and individuals of terrestrial ferns in each quadrant and the total number of individuals. Data analysis was carried out descriptively by counting: 1) Species diversity index and 2) Morisita index. Based on the research, there are 17 types of terrestrial ferns found in the area of the Benang Stokel Tourism Forest. The most dominating species (quadrant I-X), namely Cyclosorus Interruptus [INP= 46,431], the average index of fern species diversity found in the Benang Stokel Tourism Forest area in the observation quadrant (quadrant I-X) of H’= 1.138. This diversity index is in the medium category [H'= 1,0-3,322], and the average Morisita index on the observation (quadrant I-X) is Id= 0.113 with criteria [Id<1]. It can be concluded that the distribution pattern of terrestrial ferns in the area of the Stokel Yarn Tourism Forest is uniform.